Clinical Efficacy and Safety of Gokshur (Tribulus terrestris) in the Management of Amavata (Rheumatoid arthritis) - Saznam, Anant; Kumar, Chakrapani; Tiwari, Sampurna Nand; Singh, Ajay Kr (Journal of Neonatal Surgery, 2025)
The current research aims to assess the effectiveness of Gokshur (Tribulus terrestris) kwatha in comparison to Amavata. Madhava Nidana was the first to provide a detailed account of Amavata. He dedicated an entire chapter to describe the aetio-pathology, clinical characteristics, and classifications based on Dosa-Pradhanya and Sadhya-Asadhyata of Amavata (M. N. 25). Amavata can be likened to Rheumatoid arthritis, which is a chronic, systemic inflammatory polyarthritis that predominantly impacts the small diarthrodial joints of the hands and feet in a symmetrical manner. For the first time in the literature, Cakradatta elaborates on the principles and treatment protocols for Amavata, utilizing an effective combination of medications. Subsequent authors in their works, including Chikitsa sarasamgraha (Vangasen), Yogaratnakara, Bhavaprakash, and Bhaisajya ratnavali, have discussed the condition along with treatment strategies and the incorporation of additional formulations such as decoctions, tablets, and powders